Izgovarjava v Slovarju slovenskega knjižnega jezika - Horjak, Luka (Slavistična revija, 2022)
The Slovar slovenskega knjižnega jezika (Dictionary of the Slovenian standard language, SSKJ) is a fundamental dictionary of the Slovenian language which also contains information on pronunciation. Stanislav Škrabec influenced the notation of pronunciation in the SSKJ through Maks Pleteršnik’s Slovene-German dictionary. This paper presents the treatment of pronunciation in the SSKJ, in particular the contribution of Jakob Rigler, who used the survey method to prescribe the pitch accent. The main criticisms of the orthoepic part of the SSKJ by Golias, Toporišič, and Pirnat are highlighted. The extension of the pronunciation notation in the 2nd edition of the SSKJ and the current state of pronunciation notation in the 3rd edition (eSSKJ), which does not bring any significant theoretical and methodological progress compared to the first edition, are briefly discussed.
Keywords: fonetična transkripcija; fonetika; fonologija; phonetic transcription; phonetics; phonology; Slovene; slovenščina